Tren Penelitian Pengembangan LKPD Project Based Learning (PjBL) Terintegrasi Pendekatan Green Chemistry: Systematic Literature Review - Ria Zulfa; Muntari Muntari; Yunita Arian Sani Anwar (Indonesian Publication Center, 2023)
This study aims to identify and analyse research trends in the development of LKPD project-based learning integrated with green chemistry approach in chemistry learning. This research is a qualitative research with descriptive analytical method that explains the data obtained in detail and systematically with research procedures using PRISMA. The data used in this study were obtained from Google Scholar indexed documents from 2015-2023 using Publish or Perish and Dimension.ai. The type of data identified and analysed in the form of publications, publication sources, research titles, and keywords related to the development of LKPD project-based learning integrated green chemistry approach that is widely cited. The data analysis method used is bibliometric analysis assisted by VOS viewer software. The results of the analysis show that the trend of research on the development of project-based learning frameworks integrated with the green chemistry approach indexed by Google Scholar from 2015 to 2023 has increased dramatically from the previous year. There are many documents in the form of articles, proceedings, and books that discuss research on the development of LKPD project-based learning integrated green chemistry approach. The keywords that are often used in research on this subject are society, environment, technology, project models, development, science, education, etc.